Overconfidence Can Improve an Agent's Relative and Absolute Performance in Contests - Sandra Ludwig; Philipp C. Wichardt; Hanke Wickhorst (Verein für Socialpolitik, 2010)
This paper suggests a potential rationale for the recent empirical finding that overconfident agents tend to self-select into more competitive environments (e.g. Dohmen and Falk, 2006). In particular, it shows that moderate overconfidence in a contest can improve the agent's performance relative to an unbiased opponent and can even lead to an advantage of the overconfident agent in absolute terms.
Keywords: D21; D44; D82; 330; Overconfidence; Contests